Sex differences in coronary microvascular resistance measured by a computational fluid dynamics model - Taylor, Daniel J.; Aubiniere-Robb, Louise; Gosling, Rebecca; Newman, Tom; Hose, D. Rodney; Halliday, Ian; Lawford, Patricia V.; Narracott, Andrew J.; Gunn, Julian P.; Morris, Paul D. (Frontiers in Cardiovascular Medicine, 2023)
Background Increased coronary microvascular resistance (CMVR) is associated with coronary microvascular dysfunction (CMD). Although CMD is more common in women, sex-specific differences in CMVR have not been demonstrated previously. Aim To compare CMVR between men and women being investigated for chest pain. Methods and results We used a computational fluid dynamics (CFD) model of human coronary physiology to calculate absolute CMVR based on invasive coronary angiographic images and pressures in 203 coronary arteries from 144 individual patients. CMVR was significantly higher in women than men (860 [650–1,205] vs. 680 [520–865] WU, Z = −2.24, p = 0.025). None of the other major subgroup comparisons yielded any differences in CMVR. Conclusion CMVR was significantly higher in women compared with men. These sex-specific differences may help to explain the increased prevalence of CMD in women.